The Influence of Market Orientation and Digital Innovation on Marketing Performance: Study on Food and Beverage MSMEs in Surabaya - Sabriantoni, Ferdy; Indarwati, Tias Andarini (CV ODIS, 2023)
Marketing performance is a measure used by management to assess and evaluate the effectiveness and returns of marketing activities, especially sales and market share. Several factors that can affect marketing performance are market orientation and digital innovation. This study discusses the effect of market orientation and digital innovation on marketing performance in food and beverage MSMEs in Surabaya. This research is quantitative. The sampling technique used was a purposive sampling technique with 99 MSME respondents. The questionnaires were distributed offline with the measurement of answers using a four-level Likert scale. The statistical analysis used is multiple linear regression using the SPSS application. The results showed that market orientation and digital innovation affected marketing performance. The implications based on this research indicate that MSMEs are expected to implement a Market Orientation strategy to respond to better market demand and MSME players are expected always to carry out Digital Innovation to increase market reach as well as improve their business services and operations, so that their Marketing Performance will increase.